U-Pb single zircon grain dating of Present fluvial and Cenozoic aeolian sediments from Gabon: consequences on sediment provenance, reworking, and erosion processes on the equatorial West African margin - (:unkn) unknown (My University, 2008)
U-Pb ages obtained from detrital zircon from terrigenous sediments are used to determine the sources. Present fluvial sand-bars of the Ogooue river yield age spectra of detrital zircons in agreement with Archean and Early Proterozoic Sources found in the drainage. The large proportion of Late Proterozoic zircons cannot be derived from primary erosion of the watershed basement rocks, since there is no formation of that age in the area. This later group of zircons is in good agreement with reworking of the aeolian Paleogene Bateke Sands, by regressive erosion in the upper reaches of the Ogooue river, as they contain a majority of Late Proterozoic age zircons. The sources of Late Proterozoic zircons in the Bateke Sand are very distant, and transported and reworked - at least in part - by aeolian processes. Our results, together with the widely distributed Paleogene sediments over continental Africa, suggests that Paleogene was it time of subdued erosion of the cratonic areas and extensive reworking, transport and deposition within continental Africa. In contrast, our results from the Ogooue river indicate active present incision of the cratonic area, erosion of the previous continental sediments, and export of the river bed-load to the continental margin. This temporal evolution of erosion-transport-deposition is correlated with the drastic climate change that occurred during the Cenozoic, leading to a more efficient mechanical erosion, and it correlates with the increase of terrigenous flux to the margin, observed during the Neogene.
Keywords: African Research